Personal Hygiene pada Masyarakat dengan Keluhan Penyakit Kulit di Daerah Pinggiran Sungai - Aridamayanti, Bernadetta; Agianto, Agianto; Septiany, Maulidya; Chrisnawati, Chrisnawati; Khairina, Nora; Amilia, Emilda; Fayza, Egidia Nur; Vebrina, Elyza (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2024)
Geographically, the working area of the West Martapura Community Health Center has health complaints that are often encountered among Indonesian people, especially those living in river basin areas, namely skin health problems. In skin diseases, behavioral and attitudinal factors are often associated with aspects of personal hygiene, so that people with poor hygiene have the potential to cause and spread disease. There has been no research that has conducted research on at-risk communities such as riverside communities which are wetland environments with a preventive killing approach. This research aims to determine the description and provide interventions regarding personal hygiene in people with complaints of skin diseases with a quantitative design. Primary data collection techniques were obtained from the results of filling out questionnaires and presented in table form and analyzed descriptively. Regarding personal hygiene in people with complaints of skin diseases in riverside areas, it was found that 245 (54.8%) respondents had good personal hygiene.